PENERAPAN METODE EKSPERIMEN UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS II SDN 24 CAKRANEGARA - I GUSTI AYU NITA ARINI (GANEC SWARA, 2018)
This research is a Classroom Action Research (CAR) which consists of two cycles in which each cycle consists of four stages: planning, implementation, observation, and reflection. The background of this research is that the learning outcomes of students have not yet reached the KKM.This study aims to find out whether the application of experimental methods in PBM can improve the learning outcomes of 2nd grade students of SD Negeri 24 Cakranegara in the first semester of the 2017/2018 academic year. The research takes place at SDN 24 Cakranegara, for 5 (five) months from August to December 2017 with research subjects of 2nd grade students with 33 people in total. Observation, evaluation, and documentation are used for data collection. While, the data analysis techniques used are qualitative and quantitative descriptive. In the study, performance indicators for learning outcomes have been established; if 85% of students achieve a score of 70. The indicator is reached in cycle II, so the action research is carried out in 2 cycles.        The results show that the use of the experimental method in PBM could improve the learning outcomes of science in the 2nd grade students of SD Negeri 24 Cakranegara. This is evident from the average score in the first cycle of 71.5 increasing to 89 in the second cycle, with the level of student completeness from 52% in the first cycle increased to 92% in the second cycle.